Accepting video conferencing technology as an in-service training tool for health professionals - Unal, Rabia; Yilmaz, M. Betul (SPRINGER, 2024)
This study investigates healthcare professionals' acceptance of video conferences for in-service training in terms of performance expectancy and social influence. Furthermore, it attempts to determine which properties of video conferences influenced and predicted the adoption of video conferencing technology. We employed the cross-sectional survey research design, one of the descriptive research designs. The participants consisted of 181 physicians from a medical specialty society. To collect data, we used the Unified Theory of Acceptance and Use of Technology-2 (UTAUT-2) scale. Findings revealed that being able to ask questions during the video conferences, not paying for participation, timing problems, and lack of social interaction predicted the acceptance of video conferences for in-service training regarding performance expectancy and social influence among physicians. This article offers practical recommendations for professionals to adopt and maximize the use of videoconferencing for in-service training. The findings of this study will shed light on future practices and studies regarding the use of video conferencing systems for in-service training by revealing the preferences of physicians and the factors affecting their acceptance behavior.
Keywords: Video conferencing; Technology acceptance; In-service training; Physicians; INFORMATION-TECHNOLOGY; ACCEPTANCE MODEL; STUDENT; Education & Educational Research